Comprometimento com a organização e a carreira: avaliação do grau de comprometimento dos gerentes e especialistas de uma grande empresa siderúrgica - Lauro Cesar de Abreu (2004)
To face the growing competition that they are submitted to, organization of all corners of the world are aiming at implementing different strategies of modernization, not only in the technological scenario, but also in the organizational one. In this attempt of becoming adequate to this new environment, the companies are looking for competitive differentials inwhich they could hold on. However, those strategies are frustrated or loose their effectiveness if the companies do not have a set of human resource committed with the organization and with their own work. In this context, the research on work commitment has been a current issue, being the object of study of a great number of managers and researches. In order to add an extra contribution to the subject, this study was conducted in a great Brazilian Steel Plant, a highly competitive organization that operates in world markets of semi-finished steel products, being the worlds leader exporter of steel plates. Using previously tested and validated models, the levels of commitment of managers (3 groups) - and other graduated professionals that were engaged in important positions within the company - were researched. A total of 172 professionals participated. In this study five dimensions of work commitment were analyzed, two of those referred to the following focus: Organizational commitment and career commitment, and three referred to the affective, normative and instrumental components of the organizational commitment. To determine differentiated profiles of theresearched professionals, and therefore measure the level of commitment, the cluster analysis method was used in two different ways: a) Simultaneously using the five dimensions analyzed; b) separately using the two dimensions that referred to the focus, and the two thatreferred to the components. The results found in this study indicated a dual commitment: an organizational and a career commitment. The results also showed that for the four groups there is a high level of commitment. As for the focus, the organizational commitment prevailed, and for the components, the affective commitment was the most prominent. Finally, the academic and practical implications are presented, as well as the limitations and recommendations to future research on the field.